UBE2L3 Suppresses Oxidative Stress-regulated Necroptosis to Accelerate Osteosarcoma Progression - Zhao, Xiwu; Shan, Guoqiang; Xing, Deguo; Gao, Hongwei; Xiong, Zhenggang; Hui, Wenpeng; Gong, Mingzhi (Recent Patents on Anti-Cancer Drug Discovery, 2025)
BackgroundOsteosarcoma is a highly invasive bone marrow stromal tumor with limited treatment options. Oxidative stress plays a crucial role in the development and progression of tumors, but the underlying regulatory mechanisms are not fully understood. Recent studies have revealed the significant involvement of UBE2L3 in oxidative stress, but its specific role in osteosarcoma remains poorly investigated.ObjectiveThis study aimed to explore the molecular mechanisms by which UBE2L3 promotes oxidative stress-regulated necroptosis to accelerate the progression of osteosarcoma using in vitro cell experiments.MethodsHuman osteoblast hFOB1.19 cells and various human osteosarcoma cell lines (MG-63, U2OS, SJSA-1, HOS, and 143B) were cultured in vitro. Plasmids silencing UBE2L3 and negative control plasmids were transfected into U2OS and HOS cells. The cells were divided into the following groups: U2OS cell group, HOS cell group, si-NC-U2OS cell group, si-UBE2L3-U2OS cell group, si-NC-HOS cell group, and si-UBE2L3-HOS cell group. Cell viability and proliferation capacity were measured using the Tunnel method and clonogenic assay. Cell migration and invasion abilities were assessed by Transwell and scratch assays. Cell apoptosis was analyzed by flow cytometry, and ROS levels were detected using immunofluorescence. The oxidative stress levels in various cell groups and the expression changes of necroptosis-related proteins were assessed by PCR and WB. Through these experiments, we aim to evaluate the impact of oxidative stress on necroptosis and uncover the specific mechanisms by which targeted regulation of oxidative stress promotes tumor cell necroptosis as a potential therapeutic strategy for osteosarcoma.ResultsThe mRNA expression levels of UBE2L3 in human osteosarcoma cell lines were significantly higher than those in human osteoblast hFOB1.19 cells (p <0.01). UBE2L3 expression was significantly decreased in U2OS and HOS cells transfected with si-UBE2L3, indicating the successful construction of stable cell lines with depleted UBE2L3. Tunnel assay results showed a significant increase in the number of red fluorescent-labeled cells in si-UBE2L3 groups compared to si-NC groups in both cell lines, suggesting a pronounced inhibition of cell viability. Transwell assay demonstrated a significant reduction in invasion and migration capabilities of si-UBE2L3 groups in osteosarcoma cells. The clonogenic assay revealed significant suppression of proliferation and clonogenic ability in both U2OS and HOS cells upon UBE2L3 knockdown. Flow cytometry confirmed that UBE2L3 knockdown significantly enhanced apoptosis in U2OS and HOS cells. Immunofluorescence results showed that UBE2L3 silencing promoted oxidative stress levels in osteosarcoma cells and facilitated tumor cell death. WB analysis indicated a significant increase in phosphorylation levels of necroptosis-related proteins, RIP1, RIP3, and MLKL, in both osteosarcoma cell lines after UBE2L3 knockdown. In addition, the expression of necrosis-associated proteins was inhibited by the addition of the antioxidant N-acetylcysteine (NAC).ConclusionUBE2L3 is upregulated in osteosarcoma cells, and silencing of UBE2L3 promotes oxidative stress in these cells, leading to enhanced necroptosis and delayed progression of osteosarcoma.
Keywords: oxidative stress